Communication Competence of Islamic Religious Counselors in Preventing Early Marriage Through Guidance for School-Age Adolescents (BRUS) at State Vocational School 2 Barru - Nur Asmi Hadrayani; Ramli; Muhammad Qadaruddin; Iskandar; Sumarni Sumai (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study discusses the Communication Competence of Islamic Religious Counselors in Preventing Early Marriage Through Guidance for School-Age Adolescents (BRUS) at SMK Negeri 2 Barru. The background of this study is based on the high number of early marriages which have a negative impact on education, health, and the future of adolescents, so that an active role of religious counselors is needed as agents of change in providing education and guidance to adolescents. This study uses a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving religious counselors, teachers, and students as informants. The results of the study indicate that (1) religious counselors have communication competencies that include interpersonal communication skills, persuasive communication, dialogic and empathetic in order to build emotional closeness with students. (2) The BRUS program at SMK Negeri 2 shows positive achievements thanks to the support of various supporting factors, including the openness of the school, the competence of religious counselors in effective and contextual communication, and active student participation. (3) The communication strategy used by Islamic religious counselors in the BRUS program at SMK Negeri 2 Barru has proven effective in preventing early marriage. A persuasive approach through emotional, rational, and religious aspects successfully touches both the affective and cognitive aspects of students, thus encouraging conscious attitude change. This strategy is complemented by the use of communicative and contextual communication tailored to the background and dynamics of students' lives. Although this approach is relevant to the needs of adolescents, its effectiveness still needs to be improved through flexible time planning, small guidance groups, and cross-sector collaboration.